Inhibition of miR-27b Regulates Lipid Metabolism in Skeletal Muscle of Obese Rats During Hypoxic Exercise by Increasing PPARγ Expression - Wang, Xuebing; Lu, Yingli; Zhu, Lei; Zhang, Haibo; Feng, Lianshi (Frontiers in Physiology, 2020)
Hypoxic exercise may represent a novel therapeutic strategy to reduce and prevent obesity through the regulation of lipid metabolism. During hypoxic exercise, the targeting of peroxisome proliferator-activated receptor gamma (PPARγ) by miR-27b has been proposed to be one of the mechanisms involved in the modulation of lipid metabolism. We have previously shown that miR-27b can repress PPARγ and lipid metabolism-associated factors, thereby affecting lipid metabolism during hypoxic exercise in a rat model of obesity. In the current study, we aimed to confirm the role of miR-27b in the regulation of lipid metabolism. First, miR-27b expression was either upregulated or downregulated through the injection of adeno-associated virus (AAV) 9 containing a miR-27b expression cassette or miR-27b-3p inhibitor, respectively, into the right gastrocnemius muscle of obese rats. The rats were then subjected to a four-week program of hypoxic exercise, and a series of parameters related to lipid metabolism were systematically evaluated, including body composition, blood lipid levels, miR-27b RNA levels, and mRNA and protein levels of PPARγ and those of its downstream lipid metabolism-associated factors. No significant differences were found in body composition between rats expressing different levels of miR-27b. However, regarding blood lipids, miR-27b overexpression led to increased concentrations of triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and free fatty acids (FFAs), while inhibition of miR-27b decreased the total cholesterol (TC) level and increased that of high-density lipoprotein cholesterol (HDL-C). At the mRNA level, miR-27b overexpression downregulated the expression of Pparγ, but upregulated that of lipid metabolism-associated factors such as heart-type fatty acid-binding protein (H-FABP), fatty acid transport protein 1(FATP1), adipose triglyceride lipase (ATGL), and lipoprotein lipase (LPL), whereas miR-27b inhibition elicited the opposite effect; however, inhibition of miR-27b led to elevated cholesterol 7 alpha-hydroxylase(CYP7A1) and fatty acid translocase 36 (CD36) levels. Similarly, at the protein level, miR-27b overexpression promoted a decrease in the concentration of PPARγ, whereas miR-27b inhibition led to an increase in PPARγ levels, as well as those of CYP7A1, CD36, ATGL, and LPL. Overall, our results indicated that hypoxic exercise regulates lipid metabolism via the miR-27b/PPARγ pathway and modulates ATGL and LPL expression through inducing their posttranscriptional modifications.